Impact of Blockchain Technology In Agriculture Supply Chain a Comprehensive Review of Applications, Challenges, and Future Directions - Gurusamy, UmaMaheswari; Vijayarajan, Sangeetha; Gunasekaran, Praveen Kumar; Anantharaman, Meenakshi (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: This review paper examines the transformative potential of blockchain technology in addressing critical challenges within agricultural supply chains, including traceability, transparency, fraud prevention, and equitable value distribution. It aims to synthesize existing research and real-world applications to highlight how blockchain can create more efficient, sustainable, and fair food systems. Methodology/Approach: The study adopts a systematic literature review methodology, analyzing peer-reviewed articles, industry reports, and case studies from 2008 to 2024. Key frameworks and implementations, such as IBM Food Trust, AgriDigital, and TE-FOOD, are evaluated to identify patterns, benefits, and limitations of blockchain adoption in agriculture. Originality/Relevance: This paper contributes to the growing body of research on blockchain in agriculture by integrating insights from decentralized finance (DeFi), IoT, and AI, offering a holistic view of next-generation supply chains. It addresses gaps in scalability, regulatory challenges, and adoption barriers while proposing future trends like tokenization and predictive analytics. Key Findings: Blockchain enhances traceability, reducing food fraud and enabling rapid contamination tracking (e.g., Walmart’s mango traceability in 2.2 seconds). Smart contracts automate payments and compliance, empowering smallholder farmers with timely compensation. Integration with IoT and AI improves real-time monitoring and demand-supply matching, fostering sustainability. Challenges include scalability limitations, regulatory ambiguities, and the digital divide in rural areas. Theoretical/Methodological Contributions: The paper advances theoretical understanding by linking blockchain to ethical sourcing, sustainability, and farmer empowerment. Methodologically, it provides a framework for evaluating blockchain’s role in multi-stakeholder supply chains, emphasizing hybrid architectures and decentralized verification. The findings underscore blockchain’s potential as a foundational technology for equitable and resilient food systems.